2020
DOI: 10.1017/s0950268820002083
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between clinical outcomes and empirical antibiotic therapy in patients with community-onset Gram-negative bloodstream infections: a cohort study from a large teaching hospital

Abstract: The relationship between clinical outcomes and empirical antibiotic therapy in patients with community-onset Gram-negative bloodstream infections: a cohort study from a large teaching hospital. Epidemiology and Infection 148, e225, 1-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Discordant empirical antimicrobial therapy was defined as active antimicrobial therapy not administered within 48 hours after obtaining blood culture samples. 27 28 …”
Section: Methodsmentioning
confidence: 99%
“…Discordant empirical antimicrobial therapy was defined as active antimicrobial therapy not administered within 48 hours after obtaining blood culture samples. 27 28 …”
Section: Methodsmentioning
confidence: 99%
“…We speculate that this may be due to the fact that patients received AUEAT were worse off, as they were older and had a higher proportion of fever, treat with vasopressor, and use mechanical ventilation. Illness severity and age were independent predictors of mortality 29,30 . Actually, age and illness severity are correlated.…”
Section: Discussionmentioning
confidence: 95%
“…However, the relationship between inappropriate empiric treatment and outcome is conflicting. Aryee et al [62] found that 14.6% of patients with community-acquired GNBSI received inappropriate empiric treatment. Inappropriate treatment was associated with in-hospital mortality for K. pneumoniae BSI but not for Escherichia coli BSI, the latter mostly from a urinary source.…”
Section: Empiric Treatmentmentioning
confidence: 99%